2019
DOI: 10.3390/ijerph16060908
|View full text |Cite
|
Sign up to set email alerts
|

Race-, Age-, and Anatomic Site-Specific Gender Differences in Cutaneous Melanoma Suggest Differential Mechanisms of Early- and Late-Onset Melanoma

Abstract: In order to explore melanoma risk factors through gender-, age-, race-, and site-specific incidence rates, malignant melanoma cases from the Caucasian whites and non-whites were retrieved from the US SEER database. Age-standardized, age-, and site-specific tumor rates were calculated. All races and both genders showed positive annual average percentage changes (AAPCs) over the years, but AAPCs varied at different body sites, with men’s trunk exhibiting the fastest increase. Non-whites were diagnosed at a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 37 publications
(56 reference statements)
7
31
2
2
Order By: Relevance
“…Malignant melanoma is one of the most aggressive malignancies 26 . The epidemiology of malignant melanoma in Europe is based on three main factors; age (over 40 y), male gender, and location (head/neck, trunk, upper and lower extremity) [27][28][29][30] . The incidence of MM in Europe is increasing at a rate of 3-7%, 144,000 new cases per year, and 27,000 deaths per year 31 .…”
mentioning
confidence: 99%
“…Malignant melanoma is one of the most aggressive malignancies 26 . The epidemiology of malignant melanoma in Europe is based on three main factors; age (over 40 y), male gender, and location (head/neck, trunk, upper and lower extremity) [27][28][29][30] . The incidence of MM in Europe is increasing at a rate of 3-7%, 144,000 new cases per year, and 27,000 deaths per year 31 .…”
mentioning
confidence: 99%
“…The GENEVA samples were potentially able to call all potential SNPs, and therefore, this might be another reason that we could not replicate the findings. Nevertheless, as demonstrated in our series of publications [2][3][4]7,81], the gender difference in melanoma incidence is significant but not yet fully explained. Meanwhile, studies on hormone impact on melanoma are still ongoing in our lab and other research groups.…”
Section: Discussionmentioning
confidence: 70%
“…CM ranked second in the national trends in rates of new cancer cases in both genders [1]. We and others have shown that there is a distinct age-and sex-dependent incidence pattern of CM [2][3][4][5][6]. Specifically, the incidence rates are higher in older men (>~50 years) but lower in younger men as compared to women of the same ages [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Variables such as age at diagnosis, gender, race (White, Black, American Indian/AK Native (AIAN), and Asian/Pacific Islander (API)), origin (Non-Hispanic and Hispanic), year of diagnosis, primary laterality (left, right, bilateral, and side unspecified), histological type, AJCC stage, stage at diagnosis (localized, regional, and distant), metastasis, surgery, radiation, and chemotherapy were extracted [ 17 ]. Histologic characteristics were categorized as melanoma not otherwise specified (NOS), Lentigo malignant melanoma (LMM), superficial spreading melanoma (SSM), nodular melanoma (NM), and others.…”
Section: Methodsmentioning
confidence: 99%